Total Synthesis of a Partial Structure from Arabinogalactan and Its Application for Allergy Prevention. Issue 3 (27th October 2020) - Krumb, Matthias; Jäger, Maximilian; Voss, Alice; Immig, Loreen; Peters, Karin; Kowalczyk, Danuta; Bufe, Albrecht; Opatz, Till; Holst, Otto; Vogel, Christian; Peters, Marcus
Abstract: Arabinogalactan, a microheterogeneous polysaccharide occurring in plants, is known for its allergy‐protective activity, which could potentially be used for preventive allergy treatment. New treatment options are highly desirable, especially in a preventive manner, due to the constant rise of atopic diseases worldwide. The structural origin of the allergy‐protective activity of arabinogalactan is, however, still unclear and isolation of the polysaccharide is not feasible for pharmaceutical applications due to a variation of the activity of the natural product and contaminations with endotoxins. Therefore, a pentasaccharide partial structure was selected for total synthesis and subsequently coupled to a carrier protein to form a neoglycoconjugate. The allergy‐protective activity of arabinogalactan could be reproduced with the partial structure in subsequent in vivo experiments. This is the first example of a successful simplification of arabinogalactan with a single partial structure while retaining its allergy‐preventive potential. Abstract : Total synthesis of a pentasaccharide containing l ‐arabinose‐ and d ‐galactose was accomplished and covalently coupled to a carrier protein to form a neoglycoconjugate that mimics partial structures of allergy‐preventive arabinogalactan. Inhalative treatment of mice with the neoglycoconjugate protects them against allergic inflammation by the induction of immune regulation involving antibodies and interleukin‐10.